Selective lipase-catalyzed preparation of diol monobenzoates by transesterification and alcoholysis reactions in organic solvents - E. Santaniello; P. Ciuffreda; ALESSANDRINI, LAURA; A. Repetto; S. Casati (Journal of Molecular Catalysis B: Enzymatic, 2006)
Lipases from Mucor miehei (MML) and Candida antarctica (CAL) are able to catalyze the monobenzoylation of the primary hydroxy group of 1,2- 1,4- or 1,5-diols with vinyl benzoate in an organic solvent, the reaction proceeding with high regioselectivity and moderate enantioselectivity. The lipase-catalyzed debenzoylation of 1,2-propanediol dibenzoate by alcoholysis with I-octanol most satisfactorily occurred with Pseudomonas cepacia lipase absorbed onto celite that allowed also to prepare (R)-1-benzoyloxy-2-methylpropan-3-ol from 2-methyl-1,3-propanediol dibenzoate, a result complementary to MML-catalyzed benzoylation of 2-methyl-1,3-propanediol that affords the (S)-monobenzoate.